2005
DOI: 10.1128/jvi.79.19.12602-12607.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Bunyamwera Virus mRNA Transcription Signal Resides within both the 3′ and the 5′ Terminal Regions and Allows Ambisense Transcription from a Model RNA Segment

Abstract: Bunyamwera virus (BUNV) is the prototype of the Bunyaviridae family of RNA viruses. BUNV genomic strands are templates for both replication and transcription, whereas the antigenomic RNAs serve only as templates for replication. By mutagenesis of model templates, we showed that the BUNV transcription promoter comprises elements within both the 3 and the 5 nontranslated regions. Using this information, we designed a model ambisense BUNV segment that transcribed BUNV S mRNA from the genomic strand and green fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The parental construct for these deletions was the previously described model segment 25/25 (Barr et al 2005), which contained the first 25 nt of both 39 and 59 S segment NTRs, and which replicated with an ability approaching that of the wild type. A total of five model segments having deletions within their anti-genomic 39 ends were constructed and were designated 25/23, 25/21, 25/18, and 25/17, with the numbers corresponding to the lengths of the 59 and 39 anti-genomic NTRs, respectively.…”
Section: Defining the Minimal Promoter For Replication And Encapsidationmentioning
confidence: 99%
See 2 more Smart Citations
“…The parental construct for these deletions was the previously described model segment 25/25 (Barr et al 2005), which contained the first 25 nt of both 39 and 59 S segment NTRs, and which replicated with an ability approaching that of the wild type. A total of five model segments having deletions within their anti-genomic 39 ends were constructed and were designated 25/23, 25/21, 25/18, and 25/17, with the numbers corresponding to the lengths of the 59 and 39 anti-genomic NTRs, respectively.…”
Section: Defining the Minimal Promoter For Replication And Encapsidationmentioning
confidence: 99%
“…Therefore, when we aligned the 59 bound RNA sequences, we also included the BUNV 59 NTRs in the analysis. Furthermore, as our previous work showed that just 25 nt at the 59 end of the S segment is sufficient for replication and thus encapsidation of either BUNV genomic or anti-genomic strands (Barr et al 2005), we included only these nucleotides in the alignment. Our analysis failed to detect any common motifs within these sequences, and thus suggested that the bound RNAs were unlikely to be encapsidated by virtue of a specific signal formed by a linear nucleotide sequence.…”
Section: Analysis Of Rna Bound To the Tetramersmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant examples are the promoter models for influenza A virus (2, 6-8, 10, 11, 15, 16, 22, 24, 26), Thogoto virus (19,20), Bunyamwera virus (3,4,17), and Uukuniemi virus (9). Great similarity in structure and function is seen between the Lassa virus, Uukuniemi virus, and Bunyamwera virus promoters.…”
mentioning
confidence: 99%
“…Deletion analysis showed that both 3Ј and 5Ј termini are required for transcriptional activation, indicating that the promoter indeed functions as a duplex. The promoter elements of several segmented negative-strand RNA viruses, including influenza A virus (2, 6-8, 10, 11, 15, 16, 22, 24, 26), Thogoto virus (19,20), Bunyamwera virus (3,4,17), and Uukuniemi virus (9), have already been characterized in detail, and structural models of the promoter have been proposed. A detailed analysis of the arenavirus promoter is still lacking.…”
mentioning
confidence: 99%